Elementos de la administración austro-española y la administración central castellana en 1710 - Solís Fernández, José (Cuadernos de Historia del Derecho, 2011)
In 1706 and 1710 the Spanish Austrias administration considers the establishment of control systems belonging to the Crown of Castile. By this last date of 1710 a series of reports from the secretariat of Carlos of Austria is known, that allows to identify some budgets belonging to that Austrias administration and the insertion in it of the Castilian model.
Keywords: 18th century; Succession War; Archduke Carlos; Spanish Austrias administration; Government of the Crown of Castile